2023
DOI: 10.1002/uog.26180
|View full text |Cite
|
Sign up to set email alerts
|

Presurgery motor level assessment for prediction of motor level at birth in fetuses undergoing prenatal repair of open spina bifida: time to abandon anatomical level in counseling

Abstract: Objectives First, to investigate the correlation between prenatal presurgery anatomical and motor levels of the lesion with motor level at birth in cases undergoingprenatal repair of open spina bifida and, second, to identify factors leading to a loss of two or more motor levels between the presurgery and postnatal assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Our results are in agreement those of a recent study published by Maiz et al 5 . Anatomical level of the lesion and postnatal motor-function level were concordant in only 23% of cases and, comparing prenatal and postnatal motor-function levels, we found that 87% of infants presented similar or improved motor-function level in the postnatal evaluation.…”
Section: Review In Context Of Previous Studiessupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in agreement those of a recent study published by Maiz et al 5 . Anatomical level of the lesion and postnatal motor-function level were concordant in only 23% of cases and, comparing prenatal and postnatal motor-function levels, we found that 87% of infants presented similar or improved motor-function level in the postnatal evaluation.…”
Section: Review In Context Of Previous Studiessupporting
confidence: 94%
“…Anatomical level of the lesion and postnatal motor‐function level were concordant in only 23% of cases and, comparing prenatal and postnatal motor‐function levels, we found that 87% of infants presented similar or improved motor‐function level in the postnatal evaluation. Similarly, Maiz et al 5 . reported 88.5% of cases with similar and 1.9% of cases with improved postnatal motor‐function level.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…29 Ultrasound assessment of motor function was qualified according to the lower extremity movements: Level L1 corresponds to hip flexion, L2 corresponds to hip adduction, L3 corresponds to the knee extension, L4 to knee flexion, L5 to dorsal flexion of the ankle and S1 to plantar flexion of the ankle. 30 Evaluation of the posterior fossa on fetal MRI included clivussupraocciput angle (CSA) as published by Woitek et al, presence of hindbrain herniation below the foramen magnum (FM), presence of cerebellar towering, clival concavity, brainstem compression, and tectal beaking. 31 In addition, the presence of a banana sign in the suboccipital bregmatic view was analyzed on prenatal US.…”
Section: Methodsmentioning
confidence: 99%
“…Prenatal functional US was performed as previously published, including evaluation for abnormal foot position 29 . Ultrasound assessment of motor function was qualified according to the lower extremity movements: Level L1 corresponds to hip flexion, L2 corresponds to hip adduction, L3 corresponds to the knee extension, L4 to knee flexion, L5 to dorsal flexion of the ankle and S1 to plantar flexion of the ankle 30 …”
Section: Methodsmentioning
confidence: 99%